Sociodemography of genital Chlamydia trachomatis in Coventry, UK, 1992–6. Issue 2 (1st April 2000) - Winter, A J; Sriskandabalan, P; Wade, A A H; Cummins, C; Barker, P
Abstract : Objective: To describe the sociodemographic and geographic risk factors for incident Chlamydia trachomatis genital infection. Design: Cross sectional retrospective study of cases diagnosed in local genitourinary clinics. Setting: Coventry, West Midlands, from 1992 to 1996. Subjects: 582 female and 620 male Coventry residents aged 15–64 years diagnosed with one or more episodes of genital Chlamydia trachomatis infection by enzyme immunoassay. Subjects were assigned a Townsend deprivation score based on residence. The denominator population aged 15–64 years was derived from 1991 census data. Results: The mean annual incidence of genital chlamydia was 151 episodes (95% CI 140–163) per 100 000 population in men and 138 episodes (95% CI 128–149) per 100 000 population in women. Highest subgroup incidence was observed in 15–19 year old black women (2367 (95% CI 1370–4560) per 100 000), and 20–24 year old black men (1951 (95% CI 1158–3220) per 100 000). In univariate analyses, the most important risk factor for chlamydia infection in males was being black (incidence 1377 (95% CI 1137–1652) per 100 000 for black v 133 (95% CI 122–145) per 100 000 for white; RR 10.4, p<0.0001) and for women was young age (incidence 475 (95% CI 415–540) per 100 000 for age group 15–19 years v 52 (95% CI 45–60) per 100 000 for age group 25–64 years; RR 9.1, p<0.0001). In Poisson regression models of first episodes of genital chlamydia, for both males and females the effect of ethnic group could not be fully explained by socioeconomic confounding. There were significant interactions between age and ethnic group for both sexes and between age and level of deprivation for men. Geographical analysis revealed a high incidence of genital chlamydia in estates on the edge of the city as well as the urban core. Conclusions: There is a complex interaction between geographical location, age, ethnic group, and social deprivation on the risk of acquiring genital Chlamydia trachomatis in Coventry. Better population based data are needed.